Advanced Foreign Practices in the Use of Transport Services for Regional Economic Development - Karimova Shakhnoza Uktamovna (Academia Open, 2026)
General background: Transport systems serve as fundamental components in regional economic development, directly influencing interregional relations, production growth, and investment climate improvement. Specific background: Advanced countries employ digital logistics platforms, public-private partnerships, and green transport strategies to enhance economic efficiency, yet developing nations struggle to adapt these innovations systematically. Knowledge gap: Limited empirical analysis exists on how integrated transport service models—combining digitalization, PPP mechanisms, and sustainable policies—can be strategically applied to accelerate regional economic growth in emerging markets like Uzbekistan. Aims: This study examines foreign transport practices to identify effective organizational and economic mechanisms for regional development, analyzing reforms in aviation, motor transport, and digital service implementation. Results: Comparative analysis reveals that Germany's Smart Logistics increased efficiency by 25%, South Korea's PPP model reduced budget burdens by 30%, and China's Belt and Road Initiative expanded regional trade by 40%. Uzbekistan's freight volumes grew from 650 million tons (2020) to 703.6 million tons (2024), with service value rising from 75 to 108.4 trillion UZS. Novelty: The research provides integrated assessment of digital transformation, multimodal corridor development, and green mobility strategies specifically contextualized for transitional economies. Implications: Findings establish strategic directions for implementing intelligent transport systems, expanding PPP infrastructure, and strengthening regional integration to achieve sustainable economic growth.Highlight : Digital transformation improves efficiency by 25% and reduces logistics costs through AI-based management and intelligent transport systems. Public-private partnerships enable infrastructure financing with 1:1.7 investment multiplier effect while reducing state budget burden by 30%. Multimodal integration drives regional trade growth by 40% and reduces carbon emissions by 12-14% through sustainable transport policies. Keywords : Transport Infrastructure, Regional Development, Logistics Optimization, Public-Private Partnership, Sustainable Mobility